Reporting on social marketing issues - a news media analysis - Gill, Donna; Mattinson, M.; Scharl, A. (University of Western Sydney, 2008)
This paper explores online news media reporting through automated web content analysis to determine the prevalence and attitudes of social marketing issues across various countries. Results showed that Education and Work was the most commonly reported on category followed by Health Services, Family Planning, Environment, Crime and Justice and Road Safety. News media reporting in South Africa was particularly strong across Education and Work as well as Health Services. Canada recorded the highest reporting for Family Planning. New Zealand was the most prevalent reporter for the Environmental category. Crime and Justice and Road Safety only contributed a negligible amount to the overall term frequency counts across all categories. Social marketing stakeholders must continue to rally supportfrom the media in order to increase awareness of specific issues facing countries and society.